Preparation of a probiotic quinoa beverage by enzymatic hydrolysis of its starches and subsequent lactic acid fermentation - Huapaya Castillo, Carolina Stefany; Juscamaita Morales , Juan G. (Vitae, 2023)
BACKGROUND: The concern about consuming healthy foods has increased in recent years. Not only are they expected to comply with essential feeding functions, but they also provide health benefits. Probiotics are one of the main functional components expected to be present in functional foods and beverages. They provide many health benefits and stand out due to their metabolic capacities and adaptability to different habitats. In addition, Quinoa seeds contain valuable quantities of quality protein and nutritional values of carbohydrates, proteins, fats, fibers, and mineral substances for which they are considered an ideal dietary alternative. OBJECTIVES: This research aimed to elaborate on a probiotic quinoa beverage, which combines the effect of enzymatic hydrolysis of the starches obtained from its seeds with lactic acid fermentation using probiotic cultures, seeking to enhance its nutritional properties and converting it into a functional beverage. METHODS: For this, fermentations were carried out in three different concentrations of probiotic cultures (inoculum): 10%, 5%, 1%, and three other different fermentation times: 8, 10, and 12 hours. pH, Total titrable acidity expressed as lactic acid (%), reducing sugars, and soluble solids were measured. After that, the beverage was formulated with honey, carob, preservatives, and mango flavoring. RESULTS: Statistical analysis indicated optimal conditions were achieved with 10% probiotic cultures and 10 hours of fermentation. The microbiological analysis confirmed the presence of probiotic microorganisms at a concentration of 108 CFU/mL. Proximal analysis indicated that the composition contained 84.6 Kcal, 19.3 g of carbohydrates, and 1.4 g of protein per 100 g of beverage. CONCLUSIONS: The probiotic quinoa beverage was produced and can be considered in the group of plant-based foods, as well as a functional beverage, since the probiotic cultures it contains contribute to maintaining the intestinal microbiota and prevent the onset of chronic diseases.